Answer:
Explanation:
X3 - 2x2 -24x
Pulling out tje terms 3.1 pull out like factors.
X3 - 2x2-24x =x(x2-24)
Trying the factor by spitting the middle term
3.2 factoring x2 -2x-24
The first term is x2 its coefficient is 1
The middle is -x2 its coefficient is -2
The last term is constant is -24
Multiple the coefficient of the first term by the constant 1 .-24=-24
Find the to factors of -24 whose sum eqyals the coefficient of the middle term which is -2
-24+1=-23
-12+2=-10
-8+4= -2
A d tbe final results: ×.(×-6)
Give me a five star if you got it